Multi Operator BTS Aesthetic Tower Design for Metropolitan City - Windharto, A.; Setiawan, A. (Cranfield University Press, 2009)
The growth of wireless and mobile technology stimulate development of telecommunication infrastructure, Placement of BTS (Base Transceivers Station) tower in the city cause environmental problems by inadequate space while operators install their own Tower lead to “tower forest” that caused aesthetic disruption and other social problems. The method is Concurrent engineering-Integrated Digital Design for good quality, cost, delivery and so all important process can be conducted simultaneously. The result is 3D geometry and photorealistic image for decision makers. The Implementation are Aesthetic BTS Tower as lighting tower, church tower and adaptable for any city needs of icon and landmark.
Organised by: Cranfield University
Keywords: Aesthetic BTS City Tower; Design; Multi operator